Researcb on Progress of Identifier Mecbanisms in Future Internet Arcbitecture - Ling Cai; Jinkuan Wang (Dianxin kexue)
The identifier system of current internet is based on IP address and characterized by binding the identity and location, so it can't adapt well to multi-demands of future internet, such as scalability, mobility and safety. The various international mainstream identifier systems of future internet architecture were classified firstly, which were summed up along the two development routes, one was incremental route, and another was clean-slate route. Then the challenges of design solution should be meet were analyzed. In addition, with the development trend of the internet architecture, some advices of evolution and development of the identifier system were proposed.